Janinos Degutytės ankstyvosios poezijos embleminis kraštovaizdis - Raškevičiūtė, Jurgita Žana Žana (Literatūra, 2011)
Straipsnyje aptariami ankstyvieji Janinos Degutytės poezijos rinkiniai, savo pasirodymo laikotarpiu sulaukę didžiulio skaitytojų dėmesio. Straipsnyje mėginama suvokti šios poezijos galią veikti anuomet, jos parašymo ir skaitymo laikotarpiu, ją sugrąžinant į sociokultūrinį ir biografinį kontekstą. Pasitelkus embleminio kraštovaizdžio konceptą, straipsnyje aptariama, iš kokios kultūrinės situacijos kyla embleminis Janinos Degutytės kraštovaizdis ir kokią funkciją jis atlieka tuometėje sociokultūrinėje terpėje. Argumentuojama, kad kuriant embleminį kraštovaizdį perimamas ir siekiamas perduoti simbolinis lietuviškumo modelis, kurio formavimas tuometėje sociokultūrinėje terpėje buvo intensyvi pastanga užpildyti dėl sovietinės ideologijos atsiradusią tuštumą ir pateikti modelį, galintį organizuoti kultūrinę savivoką.Eblematic landscape in the early poetry of Janina DegutytėJurgita Žana RaškevičiūtėSummaryThe article analyzes the early selections of poems by Janina Degutytė (1928–1990), a famous poet of the Soviet era, whose poetry attracted wide attention among the contemporaries. The article attempts to comprehend the power and the impact of her poetry at the time it was written and read, to bring this poetry back to its socio-cultural and biographic contexts.The research focuses on the analysis of the relationship between the subject and the poetic landscape. It is considered that the landscape is a particular value-laden structure, which implies a particular notion of personhood and proposes a particular model of identity, prevailing over other possible or arrested models. The article discusses the appropriation and transmission of the specific model of Lithuanian identity through the creation of emblematic landscape. The formation of this model was an intensive effort to fill the void created by soviet ideology and provide a model for cultural awareness. The article analyzes how the creation of emblematic landscape in the conditions of the particular historical period becomes the symbolic act of cultural inheritance, appropriation of heritage in the form of taking root in a particular tradition. In that case, the emblem transmitting recognizable cultural information performs a function of restoration and reinstatement of cultural meanings.